2013
DOI: 10.1200/jco.2012.47.7521
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Exome Analysis Reveals Neoantigen-Specific T-Cell Reactivity in an Ipilimumab-Responsive Melanoma

Abstract: The evidence for T-cell-mediated regression of human cancers such as non-small-cell lung carcinoma, renal cell carcinoma, and-in particular-melanoma after immunotherapy is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
578
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 761 publications
(610 citation statements)
references
References 22 publications
11
578
1
4
Order By: Relevance
“…24,49 In this context, it is often mentioned that the tumor microenvironment plays a critical role for antitumor T cell responses, not only by inhibiting existing T cells, but also by preventing T cell priming against neoepitopes. 50,51 At the same time, it needs to be stressed that even in the context of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…24,49 In this context, it is often mentioned that the tumor microenvironment plays a critical role for antitumor T cell responses, not only by inhibiting existing T cells, but also by preventing T cell priming against neoepitopes. 50,51 At the same time, it needs to be stressed that even in the context of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the detection of T cells reacting against patient-specific mutated antigens has been related with clinical responses to IPI. [41][42][43] The determination of the repertoire of T cells reactive with both differentiation/cancer-testis and mutated TAAs along with the therapeutic usage of immunomodulatory agents need to be further dissected in MM patients. In addition, it is worthy to monitor T cell responses against tumor cells, which in our study represented a possible immunological parameter associated with the clinical outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate that neoantigens can be rapidly identified within a few weeks and can serve as tumor-specific targets for T cell-mediated recognition and destruction of tumor cells. Similarly, several neoantigens have been identified from human cancer recognized by CD8 + and CD4 + T cells through exome sequencing and screening for T cell responses [221][222][223]. More recently, it has been further demonstrated that neoantigen-specific T cells can be isolated from patient PBMCs using FACS analysis and purification, although their frequencies are much lower than neoantigen-specific T cells in the corresponding TIL populations [45,224].…”
Section: The Second Wave Of Tumor Antigen Discovery: Mutation-derivedmentioning
confidence: 99%